2021
DOI: 10.1016/j.fawpar.2020.e00103
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibodies to Toxoplasma gondii among owned dogs in Cambodia

Abstract: Toxoplasma gondii is a protozoan parasite belonging to the phylum Apicomplexa, which has a two-host life cycle and an extensive global distribution. The presence of antibodies to T. gondii was examined in owned dogs in Cambodia. In total, 103 dog serum samples from 37 households in northern Cambodia were collected and examined for evidence of T. gondii infection using an indirect immunofluorescent antibody test. In total, 52 of 103 (50.5%) samples were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…(2) Samples from Zhoukou were collected in 2015, which is relatively earlier than in cities of Zhengzhou and Puyang. Regarding T. gondii infection in this study, gender and age were not risk factors for dogs, and the lack of relationship with gender was in agreement with the findings of other studies ( Lopes et al., 2011 ; Yang et al., 2013 ; Nguyen et al., 2020 ). However, a previous study found that seroprevalence in dogs increased with age ( Dubey et al., 2020 ), which may be related to the low seroprevalence of T. gondii in dogs or small sample size in this study.…”
Section: Discussionsupporting
confidence: 93%
“…(2) Samples from Zhoukou were collected in 2015, which is relatively earlier than in cities of Zhengzhou and Puyang. Regarding T. gondii infection in this study, gender and age were not risk factors for dogs, and the lack of relationship with gender was in agreement with the findings of other studies ( Lopes et al., 2011 ; Yang et al., 2013 ; Nguyen et al., 2020 ). However, a previous study found that seroprevalence in dogs increased with age ( Dubey et al., 2020 ), which may be related to the low seroprevalence of T. gondii in dogs or small sample size in this study.…”
Section: Discussionsupporting
confidence: 93%
“…An inhouse qualitative indirect fluorescent antibody test (IFAT) was used for the detection of T. gondii antibodies in the duck serum samples. Preparation of IFAT slides: T. gondii tachyzoites of the RH strain were cultivated in vitro in African green monkey kidney (Vero) cells [ 21 , 22 ]. The monolayer of the infected cells was harvested, and T. gondii tachyzoites were released and enriched using several passages through syringe needles and a 5 μm filter.…”
Section: Methodsmentioning
confidence: 99%
“…Tachyzoites of the highly virulent T. gondii RH strain (Type I) were maintained using Vero cells in MEM with 5% FBS (Gibco, USA) and 1% penicillin-streptomycin (Gibco, USA). The T. gondii tachyzoites were cultivated every 4 days in Vero cells and collected according to published protocols [25,26].…”
Section: Mice Ethics Statement and Parasitesmentioning
confidence: 99%